Using interpretive structural modelling and quality cost model to solve project completion delay in shipyard case study in PT X - Ngurah Ayu Happy Susilawati; Desi Adhariani (Jurnal Siasat Bisnis, 2023)
Purpose – This research proposes an alternative method to solve completion delay issue and optimized the strategy using ISM technical method and Quality Cost Model application. Design/methodology/approach – Data was acquired from 120 questions from company key persons that involved in project for last 5 years. The instruments processed using ISM analysis to measure the relationship among causes, then using Quality Cost Model to solve. Findings – This research shows that factors of late payment from client, delays in bank credit processing, bad weather, and design changes by owners are the root causes of delays. Further analysis using the Theory of Constraint (TOC) shows that financial constraint issues influence the decreased throughput and increase operating cost. Further management use five sequential steps to improve the management and P-A-F models as one of strategic cost management tools applied to the root causes to determine the optimum cost strategy to solve the problem. Research limitations/implications – This research was conducted using a case study method, and the conclusion related to problem and root cause may not be applied totally to other companies, but the framework may be applicable. Future research can investigate other issue using TOC framework, combine TOC with other models to conduct root cause analysis, and the COQ model implementation in shipyard management. Practical implications – This research demonstrates that management can use Interpretative Structural Modelling (ISM) analysis to determine the root cause, then analyse and overcome the issues using TOC framework. COQ model approach to sharpening the decision, and prioritize the resources allocation. Originality/value – This research combine ISM, TOC, and PAF Quality Cost Model approach for decision making which can be a management tool in strategic cost management.